Pointing in the right direction: new developments in the field of planar cell polarity - Bayly, Roy (Nat Rev Genet, 2011)
Planar Cell Polarity (PCP) is observed in an array of developmental processes involving collective cell movement and tissue organization, and its disruption can lead to severe developmental defects. Recent studies in both flies and vertebrates have identified new functions for PCP, new signaling components, and proposed new mechanistic models. However, despite this progress, the search for simplifying principles of understanding continues and important mechanistic uncertainties still pose formidable challenges.